Elephant grass silage with addition of regional by-products - Mércia Regina Pereira de Figueiredo; Alice Cristina Bittencourt Teixeira; Luciene Lignani Bittencourt; Guilherme Rocha Moreira; Ariane Jesus Ribeiro; Frank Sinatra Gomes da Silva; André Luiz Pinto dos Santos; Maria Lindomárcia Leonardo da Costa (Acta Scientiarum: Animal Sciences, 2022)
This study examines the effect of adding coffee husks (CH), cacao by-product (CBP) and passion fruit by-product (PBP) (fresh-matter basis) in the silage of elephant grass cv. Napier on nutritional characteristics. The experiment was laid out in a completely randomized design with a 3 × 4 factorial arrangement represented by three additives (CH, CBP or PBP) and four inclusion levels (0, 12, 24 or 36%). Four replicates were used per treatment. The material was ensiled in experimental mini-silos that were opened 60 days later for chemical analysis of the produced silages. The dry matter content of the silages with CH and PBP included at levels greater than 25% was adequate. The silage with PBP inclusion showed the highest crude protein levels and the best results for in vitro dry matter digestibility. In the silage containing CH, the neutral detergent fiber content decreased linearly with increasing inclusion of the husks. The silage with CBP showed the lowest dry matter and crude protein levels and the highest pH. In conclusion, the inclusion of up to 36% PBP in the ensiling of elephant grass is recommended, as the resulting material has potential for use in ruminant feeding at times of forage scarcity.